FAKTOR RISIKO KEJADIAN TUBERKULOSIS PARU DI UNIT PELAYANAN KESEHATAN (UPK) PUSKESMAS PERUM 2 PONTIANAK - Widiyarsih, Feny; Rochmawati, Rochmawati; Saleh, Ismael (Fakultas Ilmu Kesehatan Universitas Muhammadiyah Pontianak, 2015)
Tuberculosis is not only a chronic infectious disease but also a public health problem. Pulmonary Tuberculosis spread through the droplets that come out when coughing, sneezing, and talking. The transmission of tuberculosis is strongly related to sanitary home environment, such as the condition of ventilation, the humidity and temperature of the floor, and occupancy density. The increase of the pulmonary tubercoluses cases can be seen from the data provided by the Health Care Units. The data showed that in 2011 there were 27 cases of pulmonary tuberculosis. In 2012, the cases reached 67 cases. Surprisingly, the cases of tuberculosis drastically increased to 367 cases.The study aimed at gathering the information on the risk factors of pulmonary tubercolusis cases at health care unit of Puskesmas Perum 2 Pontianak.Observational analytic and case control approach were carried out in this study. The total samples were 68 samples, consisted of cases and control group 1:1 or 34 :34. Then, each variable was tested by using chi square test.The study revealed that there were correlation of smoking habit (p value = 0,027; OR= 3,519), house sun exposure (p value = 0,028; OR= 3,429), ventilation (p value = 0,029; OR= 3,378), humidity (p value = 0,007;OR= 4,643), temperature (p value = 0,047; OR= 3,125), floor types (p value= 0,015; OR= 3,833), occupancy density (p value = 0,014;OR= 12,963), occupancy contact (p value = 0,008; OR= 4,400) and tubercolusis cases at health care unit of Puskesmas Perum 2 Pontianak.Keywords :occupation, smoking habit, occupancy contact, humidity, temperature, ventilation, house sun exposure, occupancy density, pulmonary tuberculosis.